PENGARUH INDEKS HARGA SAHAM GABUNGAN (IHSG), TINGKAT SUKU BUNGA SBI, DAN NILAI TUKAR TERHADAP UNIT PENYERTAAN REKSADANA - Christian Devi Fentikasari; Munasiron Miftah (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2014)
This study aimed to examine the effect of the Composite Stock Price Index (CSPI), SBI, and Exchange Units of Mutual Funds Against the period 2009-2011. The population in this study is a mutual fund owned Danareksa Mawar Danareksa Investment Management is active in 2009-2011. This study uses secondary data. The data analysis technique used is multiple linear regression equation kuadratterkecil and test hypotheses using t-statistics for testing the partial regression coefficients and F-statistics to test the effect together with a significance level of 5%. It also made the classic assumption test covering normality test, multicollinearity, heteroscedasticity test and autocorrelation test. The results of the study during the years 2009-2011 shows together Composite Stock Price Index (CSPI), Rate Interest Rate, and Exchange Rate Against affect Mutual Fund Units. While the Composite Stock Price Index (CSPI) and the exchange rate has an influence on Mutual Fund Units. But Interest Rates SBI has no influence Mutual Fund Units.